Pages of fashion in magazines: Alceu Penna and magazine O Cruzeiro (1950-1964) (ModaPalavra e-periódico, 2011)
This present paper aims to make considerations on a noticeable collaborator of one of the greatest magazine of Brazil’s past. This paper aims, specially, to pounder about the pages of fashion content. The magazine O Cruzeiro, that circulated from 1928 to 1975, always presented pages of fashion trends to the readers. Most of those pages were signed by a recognized illustrator, born in the state of Minas Gerais. He was Alceu de Paula Penna. Alceu Penna many times wrote and illustrated the section Costumes (Figurinos) of the magazine. Not only has he illustrated Costumes, but he was also the responsible for one of the most famous columns of the periodic: the column Girls of Alceu (Garotas do Alceu). Those pages were a mix of fashion trends, French Maisons, behavior conduct of movie stars, beauty patterns, civilities norms, and daily experiences. That was fashion transposed in pages of a magazine.
Keywords: magazine; fashion; Alceu Penna